Pendapat Ulama Madzhab Terhadap Denda Pada Praktik Mindringan - Raja Ritonga; Endah Nopita Sari (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
This research discusses about the practice of mindiringan or credit at Patiluban Mudik village Natal sub- District, Mandailing Natal Regency. Most of them work as laborer at factory, farmers, and fibrous. These works impacts their income and citizen economic, that force them to do mindiringan or credit to fulfill thie nedd every day. The practice of mindiringan or credit makes burden to them and they got fine of credit.this research is about field research by qualitative approach and the result explains as the result of observation, interviewing and documentation. Then, the data analyzes comprehensively. This research produces that the practice of credit gives the positive and negative effect for the society at the village. The positive effect is about fulfill their daily need without having money in the first time, while the negative effect is about fine if they late paying the credit in every month. There are two opinions from classical mufti about the fine in credit. First is the practice of credit is forbidden or haram because it is excessive interest or riba. The second the practice of credit is allowed for whom able to pay but they postpone it in paying and for whom are not able to pay it is forbidden.